Transfer Of antibiotic resistance gene CTX-M- An alarm for the clinician - Wahidur Rahman, Nawshad Muhammad; Lutfor, Afzalunnessa Binte; Tahmina, Sanya; Khairuzzaman, Md.; Yusuf, Md. Abdullah; Islam, Md. Zakirul; Begum, Ismat Ara (Bangladesh Journal of Medical Microbiology, 2013)
No Abstract DOI: http://dx.doi.org/10.3329/bjmm.v5i2.16416 Bangladesh J Med Microbiol 2011; 05 (02): 2-5